A BN / BiOBr heterojunction photocatalyst, a preparation method thereof and application thereof in photocatalytic nitrogen fixation

CN122999247APending Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610961614.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

目前,针对不同反应体系下如何将BiOBr与BN之间进行异质结界面优化,并将其应用于不同性质的光催化反应(如氧化反应与还原反应),依然缺乏明确的规律指导,且其在不同反应中的催化行为具有高度的不可预知性

Benefits of technology

[0028](1)本发明提供了一种BN/BiOBr异质结光催化剂及其制备方法和在光催化固氮中的应用,通过在BiOBr特定条件形成过程中引入BN纳米片,在BiOBr微米球表面构建丰富异质界面,实现了高效光催化固氮合成氨。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999247A_ABST
    Figure CN122999247A_ABST
Patent Text Reader

Abstract

The application belongs to the field of photocatalytic materials and nitrogen resource conversion technology, and relates to a BN / BiOBr heterojunction photocatalyst, a preparation method thereof and application of the BN / BiOBr heterojunction photocatalyst in photocatalytic nitrogen fixation. The preparation method is as follows: first, a bismuth nitrate solution with ethylene glycol as a solvent is prepared; then, potassium bromide and hexagonal boron nitride nanosheets are added; and finally, the BN / BiOBr heterojunction photocatalyst is prepared through a solvothermal reaction after uniform dispersion. In the application, BN nanosheets are introduced in the process of forming BiOBr under specific conditions, and a rich heterojunction interface is constructed on the surface of BiOBr microspheres, so that efficient photocatalytic nitrogen fixation and ammonia synthesis are realized, and the average ammonia generation rate can reach 282.4 μmol·g ‑1 ·h ‑1 , which is 14 times that of pure BiOBr in the same system, and the application provides a new technical route for the development of high-efficiency solar-driven nitrogen fixation and ammonia synthesis photocatalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalytic materials and nitrogen resource conversion technology, and relates to a BN / BiOBr heterojunction photocatalyst, its preparation method and its application in photocatalytic nitrogen fixation, specifically applied to the photocatalytic N2 to NH3 synthesis reaction under natural or simulated natural light and in the presence of a proton donor. Background Technology

[0002] Ammonia (NH3) is an important chemical raw material and a potential hydrogen energy carrier. Currently, industrial ammonia production mainly relies on the Haber-Bosch process, which requires operation under high temperature and high pressure conditions, resulting in high energy consumption and large amounts of carbon dioxide emissions.

[0003] Photocatalytic nitrogen fixation technology utilizes solar energy to drive the reaction of nitrogen with water to produce ammonia, directly generating ammonia under ambient temperature and pressure conditions, providing a new technological route to replace the traditional Haber-Bosch process. This technology can convert solar energy into chemical energy, simultaneously achieving efficient utilization of nitrogen and water resources, and has the advantages of being environmentally friendly, energy-efficient, and sustainable. However, due to the N... The nitrogen bond energy is as high as 941 kJ / mol, making it difficult for nitrogen to be adsorbed and activated by the catalyst. Secondly, the electron-hole pairs generated by the photocatalyst under light conditions are prone to rapid recombination, which severely limits the efficiency of photocatalytic ammonia synthesis.

[0004] Bismuth oxybromide (BiOBr), a typical bismuth-based layered semiconductor material, possesses a unique layered crystal structure that enables the formation of a built-in electric field within the crystal, thereby promoting the separation of photogenerated electrons and holes. Simultaneously, BiOBr exhibits high chemical stability, a suitable band structure, and strong UV-Vis light response, attracting widespread attention in the field of photocatalysis. However, single BiOBr still suffers from insufficient nitrogen adsorption capacity and rapid carrier recombination, limiting its practical efficiency in photocatalytic ammonia synthesis.

[0005] Hexagonal boron nitride (BN) is a two-dimensional layered material similar in structure to graphene, composed of alternating boron and nitrogen atoms. It exhibits high chemical and thermal stability, as well as a unique two-dimensional layered structure. BN nanosheets possess a large specific surface area and abundant surface exposure sites, providing more adsorption space for reactant molecules. Simultaneously, its layered structure facilitates electron migration and transport at interfaces, serving as an electron transport medium to promote the separation of photogenerated carriers in semiconductors. However, in current technologies, BN is typically used only as a small amount of additive or carrier, resulting in a low proportion in composite materials and a limited number of interfaces formed. Consequently, the full potential of BN in promoting electron transfer, enhancing reactant adsorption, and regulating the surface reaction environment has not been fully realized.

[0006] While existing technologies have disclosed some technical literature related to BiOBr and BN composite catalysts, it should be noted that, as a typical layered semiconductor, the photocatalytic activity of BiOBr depends not only on its simple physical combination with BN, but more profoundly on the matching degree of the microscopic heterojunction interface formed between it and BN. Currently, there is still a lack of clear guidelines on how to optimize the heterojunction interface between BiOBr and BN in different reaction systems and apply it to photocatalytic reactions of different properties (such as oxidation and reduction reactions), and its catalytic behavior in different reactions is highly unpredictable. Summary of the Invention

[0007] This invention addresses the shortcomings of existing technologies by providing a BN / BiOBr heterojunction photocatalyst, its preparation method, and its application in photocatalytic nitrogen fixation. Under specific preparation conditions, this invention constructs a BN / BiOBr heterojunction photocatalyst for photocatalytic nitrogen fixation by compositing hexagonal boron nitride nanosheets with BiOBr microspheres. The hexagonal boron nitride nanosheets are non-uniformly dispersed on the surface of the BiOBr microspheres, forming numerous closely contacting heterojunction interfaces between the hexagonal boron nitride and bismuth oxybromide. Simultaneously, significant interfacial electronic interactions occur between the hexagonal boron nitride and bismuth oxybromide, establishing a rapid migration channel for photogenerated electrons, promoting the separation and transport of photogenerated carriers, and suppressing electron-hole recombination. Furthermore, the introduction of hexagonal boron nitride nanosheets significantly alters the adsorption environment on the BiOBr microsphere surface, increasing the adsorption energy of nitrogen and water molecules and expanding the adsorption configuration, thereby improving the enrichment capacity and activation efficiency of reactants on the catalyst surface.

[0008] To achieve the above objectives, the present invention employs a technical solution consisting of the following technical measures.

[0009] In one aspect, the present invention provides a method for preparing a BN / BiOBr heterojunction photocatalyst, comprising the following steps:

[0010] (1) Dissolve bismuth nitrate pentahydrate in ethylene glycol to prepare a bismuth nitrate solution with a bismuth ion molar concentration of 0.02~0.06 mmol / mL;

[0011] (2) Potassium bromide and hexagonal boron nitride (BN) nanosheets were added to the bismuth nitrate solution obtained in step (1), and a mixed dispersion was obtained after uniform dispersion;

[0012] Wherein, the potassium bromide and bismuth nitrate are in equimolar amounts;

[0013] The molar ratio of the hexagonal boron nitride nanosheets to bismuth nitrate is (7~9):1;

[0014] (3) The mixed dispersion obtained in step (2) is subjected to a solvothermal reaction at a temperature of 120~140 ℃ for 12~16 h. After the time is reached, it is separated, washed and dried in sequence to prepare the BN / BiOBr heterojunction photocatalyst.

[0015] In this invention, potassium bromide is used as the bromine source in an ethylene glycol system without pH adjustment. On the one hand, ethylene glycol slows down the hydrolysis rate of the bismuth source. Combined with the crystal plane guiding effect of ethylene glycol, it induces BiOBr to crystallize highly along anisotropy and preferentially expose the highly active (110) crystal plane. On the other hand, the relatively high molar ratio of BN nanosheets exerts a microscopic spatial confinement effect, suppressing the layer thickness stacking of BiOBr, so that it forms a tight heterojunction interface with BN in the form of nanosheets. Testing showed that in the obtained BN / BiOBr heterojunction photocatalyst, BiOBr exhibits a hierarchical microsphere structure assembled from nanosheets, while BN is unevenly distributed on the surface of the BiOBr microspheres in the form of two-dimensional nanosheets, thus forming a "BN nanosheet / BiOBr microsphere" heterostructure. This structure significantly increases the contact area between the two phases, providing a continuous channel for the interfacial migration of photogenerated carriers.

[0016] The BN / BiOBr heterojunction photocatalyst prepared by the above method exhibited excellent photocatalytic ammonia synthesis performance under simulated sunlight irradiation, with an average ammonia generation rate reaching 282.4 μmol·g⁻¹. -1 ·h -1 The photocurrent response is approximately 14 times that of pure BiOBr in the same system. Furthermore, this BN / BiOBr heterojunction photocatalyst effectively promotes photogenerated electron migration and carrier separation, resulting in a photocurrent response approximately 1.8 times higher than that of pure BiOBr in the same system.

[0017] In this invention, we also conducted a single-variable comparative experiment on the molar ratio of hexagonal boron nitride nanosheets to bismuth ions. The comparison revealed that when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions increased to 7:1, the average ammonia generation rate showed a very significant leap. This is presumably because when the content of hexagonal boron nitride nanosheets is low, only limited interfacial contact can be formed, resulting in limited promotion of carrier separation and reactant adsorption. As the content of hexagonal boron nitride nanosheets increases, they gradually cover the surface of BiOBr microspheres, forming abundant interfacial contact regions. When the molar ratio of hexagonal boron nitride nanosheets to bismuth ions reaches 7:1, the optimal interfacial structure is obtained, which is beneficial for electron migration and surface reactions. However, when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions is further increased beyond 7:1, the average ammonia generation rate drops sharply. This is presumably because excessive hexagonal boron nitride nanosheets lead to the separation of too many electrons, which is detrimental to subsequent reduction reactions. However, when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions was further increased to 9:1, the average ammonia generation rate showed a significant rebound, the reason for which is currently unknown.

[0018] However, those skilled in the art should clearly understand that the photocatalytic activity of BiOBr, as a typical layered semiconductor, depends not only on its simple physical recombination with BN, but more profoundly on the matching degree of the microscopic heterojunction interface formed between BiOBr and BN. Currently, there is still a lack of clear guidelines on how to optimize the heterojunction interface between BiOBr and BN in different reaction systems and apply it to photocatalytic reactions of different properties (such as oxidation and reduction reactions), and its catalytic behavior in different reactions is highly unpredictable. For example, in oxidation reactions, the more hole-electron pairs are separated, the more holes participate in the oxidation reaction; however, in reduction reactions such as photocatalytic ammonia synthesis, excessive separation of hole-electron pairs leads to most electrons transferring to the BN surface, and the adsorption energies of N2 and H2O on the BN surface are weaker than those of BiOBr and the BN / BiOBr interface, making it difficult for some separated electrons to participate in subsequent reactions. Therefore, for photocatalytic oxidation and photocatalytic reduction reactions, the same BN / BiOBr heterojunction photocatalyst may exhibit significantly different catalytic performance. Furthermore, the examples and inferences related to catalytic performance mentioned above are insufficient to fully explain the rules. For example, the tests in this invention found that when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions reached 9:1, the average ammonia generation rate showed a significant rebound, the reason for which cannot be deduced from the above theories.

[0019] The conclusions of the above single-variable comparison experiments, compared with the currently published technical literature related to BiOBr and BN composite catalysts, reveal that the optimal molar ratio of hexagonal boron nitride to bismuth oxybromide varies significantly among BN / BiOBr composite photocatalysts based on different systems, and the applicable photocatalytic systems are also completely different. This indirectly verifies the unpredictability of their technical characteristics and effects in the absence of clear guiding principles.

[0020] In this paper, the hexagonal boron nitride (BN) nanosheets mentioned in step (2) can be commercially available nanoscale hexagonal boron nitride two-dimensional materials. It should be noted that hexagonal boron nitride nanosheets as additives and carriers are known in the prior art. Therefore, those skilled in the art can make appropriate selections based on the applicable specifications of hexagonal boron nitride nanosheets recorded in the prior art, referring to their parameters including size, morphology and purity, to choose commercially available or self-made materials.

[0021] In one preferred embodiment, the hexagonal boron nitride (BN) nanosheets in step (1) are preferably hexagonal boron nitride nanosheets with a diameter of <10 μm.

[0022] In one of the technical solutions, the uniform dispersion described in step (2) can be carried out under laboratory sample conditions. In order to avoid the volatilization of ethylene glycol, the dispersion can be carried out in a closed container at a temperature of 20~24 ℃ and a mechanical stirring rate of 300~600 rpm for 20~40 min.

[0023] In this paper, the separation, washing and drying processes all follow the conventional principles of chemical processes, and those skilled in the art can perform specific operations based on common knowledge. For example, under laboratory small sample conditions, in step (3), the precipitate is separated by filtration, then the precipitate is washed three times each with ultrapure water and anhydrous ethanol, and finally dried at a temperature of 70~80 ℃ for 8~10 h.

[0024] To facilitate the application of the obtained BN / BiOBr heterojunction photocatalyst to photocatalytic nitrogen fixation, in one preferred technical solution, the separation, washing and drying in step (3) are performed sequentially, and after drying, the process further includes grinding, preferably to 20-60 mesh.

[0025] On the other hand, the present invention also provides the application of the above-mentioned BN / BiOBr heterojunction photocatalyst in photocatalytic nitrogen fixation.

[0026] In one technical solution, the above-mentioned BN / BiOBr heterojunction photocatalyst is dispersed in an aqueous phase to prepare a catalyst dispersion with a mass concentration of 0.4~0.8 mg / mL; nitrogen gas is introduced into the catalyst dispersion at a flow rate of 50~90 mL / min, and photocatalytic reaction is carried out for 30~180 min under visible light irradiation at a wavelength of 400~700 nm and a temperature of 20~30 ℃, thereby synthesizing NH3 from nitrogen gas via photocatalysis.

[0027] The present invention has the following beneficial effects:

[0028] (1) This invention provides a BN / BiOBr heterojunction photocatalyst, its preparation method and its application in photocatalytic nitrogen fixation. By introducing BN nanosheets during the formation of BiOBr under specific conditions, a rich heterostructure interface is constructed on the surface of BiOBr microspheres, thereby realizing efficient photocatalytic nitrogen fixation and ammonia synthesis.

[0029] (2) The BN / BiOBr heterojunction photocatalyst prepared by the method of the present invention exhibits excellent photocatalytic ammonia synthesis performance under simulated sunlight irradiation, with an average ammonia generation rate of 282.4 μmol·g. -1 ·h -1 The photocurrent response is approximately 14 times that of pure BiOBr in the same system. Furthermore, this BN / BiOBr heterojunction photocatalyst effectively promotes photogenerated electron migration and carrier separation, resulting in a photocurrent response approximately 1.8 times higher than that of pure BiOBr in the same system.

[0030] (3) The BN / BiOBr interface constructed by the preparation method of the present invention under a specific reaction system can significantly enhance the adsorption capacity of N2 and H2O molecules, increase the adsorption configuration of reactants on the catalyst surface, and promote N2 activation and subsequent hydrogenation reaction process.

[0031] (4) The preparation process of this invention is simple, low in cost and easy to scale up, providing a new technical route for the development of high-efficiency solar-driven nitrogen fixation to ammonia photocatalyst. Attached Figure Description

[0032] Figure 1 This is a scanning electron microscope (SEM) image of the BN / BiOBr heterojunction photocatalyst prepared in Example 1 of the present invention.

[0033] Figure 2 This is a scanning electron microscope (SEM) image of the BiOBr photocatalyst prepared in Comparative Example 4 of this invention.

[0034] Figure 3The images show the X-ray diffraction (XRD) patterns of the photocatalyst samples prepared in Example 1 and Comparative Example 4 of this invention. BN corresponds to the hexagonal boron nitride nanosheets used in Example 1, and BiOBr corresponds to the sample prepared in Comparative Example 4.

[0035] Figure 4 This is a bar chart comparing the photocatalytic nitrogen fixation activities of the photocatalyst samples prepared in Example 1 and Comparative Example 4 of this invention. BN corresponds to the hexagonal boron nitride nanosheets used in Example 1, and BiOBr corresponds to the sample prepared in Comparative Example 4.

[0036] Figure 5 This is a comparison of the photocurrent response of the photocatalyst samples prepared in Example 1 and Comparative Example 4 of the present invention. BiOBr corresponds to the sample prepared in Comparative Example 4.

[0037] Figure 6 Figure 1 shows the adsorption model diagram and in-situ infrared spectrum of the photocatalyst samples prepared in Example 1 and Comparative Example 4 of this invention. Figure 2(a) shows the adsorption model diagram of the photocatalyst samples prepared in Example 1 and Comparative Example 4, with the left side corresponding to the sample prepared in Example 4 and the right side corresponding to the sample prepared in Example 1. Figure 3(b) shows the in-situ infrared spectrum of the photocatalyst samples prepared in Example 1 and Comparative Example 4, with the left side corresponding to the sample prepared in Example 4 and the right side corresponding to the sample prepared in Example 1.

[0038] Figure 7 The bar charts show the photocatalytic nitrogen fixation activity comparison of the photocatalyst samples prepared in Examples 1-3 and Comparative Examples 1-4 of this invention. BN corresponds to the hexagonal boron nitride nanosheets used in Example 1, and BiOBr corresponds to the sample prepared in Comparative Example 4.

[0039] Figure 8 This is a schematic diagram of the experimental apparatus used in the testing method of the present invention. Detailed Implementation

[0040] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. Those skilled in the art can refer to the content of this document to appropriately improve the process parameters. In particular, it should be noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the scope of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate changes and combinations to the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. Although it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in the present invention.

[0041] In one aspect, the present invention provides a method for preparing a BN / BiOBr heterojunction photocatalyst, comprising the following steps:

[0042] (1) Dissolve bismuth nitrate pentahydrate in ethylene glycol to prepare a bismuth nitrate solution with a bismuth ion molar concentration of 0.02~0.06 mmol / mL;

[0043] (2) Potassium bromide and hexagonal boron nitride (BN) nanosheets were added to the bismuth nitrate solution obtained in step (1), and a mixed dispersion was obtained after uniform dispersion;

[0044] Wherein, the potassium bromide and bismuth nitrate are in equimolar amounts;

[0045] The molar ratio of the hexagonal boron nitride nanosheets to bismuth nitrate is (7~9):1;

[0046] (3) The mixed dispersion obtained in step (2) is subjected to a solvothermal reaction at a temperature of 120~140 ℃ for 12~16 h. After the time is reached, it is separated, washed and dried in sequence to prepare the BN / BiOBr heterojunction photocatalyst.

[0047] In this invention, potassium bromide is used as the bromine source in an ethylene glycol system without pH adjustment. On the one hand, ethylene glycol slows down the hydrolysis rate of the bismuth source. Combined with the crystal plane guiding effect of ethylene glycol, it induces BiOBr to crystallize highly along anisotropy and preferentially expose the highly active (110) crystal plane. On the other hand, the relatively high molar ratio of BN nanosheets exerts a microscopic spatial confinement effect, suppressing the layer thickness stacking of BiOBr, so that it forms a tight heterojunction interface with BN in the form of nanosheets. Testing showed that in the obtained BN / BiOBr heterojunction photocatalyst, BiOBr exhibits a hierarchical microsphere structure assembled from nanosheets, while BN is unevenly distributed on the surface of the BiOBr microspheres in the form of two-dimensional nanosheets, thus forming a "BN nanosheet / BiOBr microsphere" heterostructure. This structure significantly increases the contact area between the two phases, providing a continuous channel for the interfacial migration of photogenerated carriers.

[0048] The BN / BiOBr heterojunction photocatalyst prepared by the above method exhibited excellent photocatalytic ammonia synthesis performance under simulated sunlight irradiation, with an average ammonia generation rate reaching 282.4 μmol·g⁻¹. -1 ·h -1 The photocurrent response is approximately 14 times that of pure BiOBr in the same system. Furthermore, this BN / BiOBr heterojunction photocatalyst effectively promotes photogenerated electron migration and carrier separation, resulting in a photocurrent response approximately 1.8 times higher than that of pure BiOBr in the same system.

[0049] In this invention, we also conducted a single-variable comparative experiment on the molar ratio of hexagonal boron nitride nanosheets to bismuth ions. The comparison revealed that when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions increased to 7:1, the average ammonia generation rate showed a very significant leap. This is presumably because when the content of hexagonal boron nitride nanosheets is low, only limited interfacial contact can be formed, resulting in limited promotion of carrier separation and reactant adsorption. As the content of hexagonal boron nitride nanosheets increases, they gradually cover the surface of BiOBr microspheres, forming abundant interfacial contact regions. When the molar ratio of hexagonal boron nitride nanosheets to bismuth ions reaches 7:1, the optimal interfacial structure is obtained, which is beneficial for electron migration and surface reactions. However, when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions is further increased beyond 7:1, the average ammonia generation rate also drops sharply. This is presumably because excessive hexagonal boron nitride nanosheets lead to the separation of too many electrons, which is detrimental to subsequent reduction reactions. However, when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions was further increased to 9:1, the average ammonia generation rate showed a significant rebound, the reason for which is currently unknown.

[0050] However, those skilled in the art should clearly understand that the photocatalytic activity of BiOBr, as a typical layered semiconductor, depends not only on its simple physical recombination with BN, but more profoundly on the matching degree of the microscopic heterojunction interface formed between BiOBr and BN. Currently, there is still a lack of clear guidelines on how to optimize the heterojunction interface between BiOBr and BN in different reaction systems and apply it to photocatalytic reactions of different properties (such as oxidation and reduction reactions), and its catalytic behavior in different reactions is highly unpredictable. For example, in oxidation reactions, the more hole-electron pairs are separated, the more holes participate in the oxidation reaction; however, in reduction reactions such as photocatalytic ammonia synthesis, excessive separation of hole-electron pairs leads to most electrons transferring to the BN surface, and the adsorption energies of N2 and H2O on the BN surface are weaker than those of BiOBr and the BN / BiOBr interface, making it difficult for some separated electrons to participate in subsequent reactions. Therefore, for photocatalytic oxidation and photocatalytic reduction reactions, the same BN / BiOBr heterojunction photocatalyst may exhibit significantly different catalytic performance. Furthermore, the examples and inferences related to catalytic performance mentioned above are insufficient to fully explain the rules. For example, the tests in this invention found that when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions reached 9:1, the average ammonia generation rate showed a significant rebound, the reason for which cannot be deduced from the above theories.

[0051] The conclusions of the above single-variable comparison experiments, compared with the currently published technical literature related to BiOBr and BN composite catalysts, reveal that the optimal molar ratio of hexagonal boron nitride to bismuth oxybromide varies significantly among BN / BiOBr composite photocatalysts based on different systems, and the applicable photocatalytic systems are also completely different. This indirectly verifies the unpredictability of their technical characteristics and effects in the absence of clear guiding principles.

[0052] In one embodiment, the bismuth ion molar concentration of the bismuth nitrate solution in step (1) is 0.02 to 0.06 mmol / mL, for example, 0.02 mmol / mL, 0.03 mmol / mL, 0.04 mmol / mL, 0.05 mmol / mL, 0.06 mmol / mL or any range or point value between them.

[0053] In this paper, the hexagonal boron nitride (BN) nanosheets mentioned in step (2) can be commercially available nanoscale hexagonal boron nitride two-dimensional materials. It should be noted that hexagonal boron nitride nanosheets as additives and carriers are known in the prior art. Therefore, those skilled in the art can make appropriate selections based on the applicable specifications of hexagonal boron nitride nanosheets recorded in the prior art, referring to their parameters including size, morphology and purity, to choose commercially available or self-made materials.

[0054] In one preferred embodiment, the hexagonal boron nitride (BN) nanosheets in step (1) are preferably hexagonal boron nitride nanosheets with a diameter of <10 μm.

[0055] In one embodiment, the uniform dispersion described in step (2) can be carried out in a closed container under laboratory conditions to avoid ethylene glycol volatilization. The dispersion is carried out at a temperature of 20-24 °C and a mechanical stirring rate of 300-600 rpm for 20-40 min.

[0056] In this paper, the separation, washing, and drying processes all follow conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge. In one embodiment, for example under laboratory small-sample conditions, in step (3), the precipitate is separated by filtration, then the precipitate is washed three times each with ultrapure water and anhydrous ethanol, and finally dried at a temperature of 70-80 °C for 8-10 h.

[0057] To facilitate the application of the obtained BN / BiOBr heterojunction photocatalyst to photocatalytic nitrogen fixation, in one preferred embodiment, the separation, washing and drying in step (3) are performed sequentially, and after drying, the process further includes grinding, preferably to 20-60 mesh.

[0058] On the other hand, the present invention also provides the application of the above-mentioned BN / BiOBr heterojunction photocatalyst in photocatalytic nitrogen fixation.

[0059] In one embodiment, the above-mentioned BN / BiOBr heterojunction photocatalyst is dispersed in an aqueous phase to prepare a catalyst dispersion with a mass concentration of 0.4~0.8 mg / mL; nitrogen gas is introduced into the catalyst dispersion at a flow rate of 50~90 mL / min, and the photocatalytic reaction is carried out for 30~180 min under visible light irradiation at a wavelength of 400~700 nm and a temperature of 20~30 ℃, thereby synthesizing NH3 from nitrogen gas via photocatalysis.

[0060] The present application will be further explained in detail below with reference to embodiments. However, those skilled in the art should understand that these embodiments are provided for illustrative purposes only and are not intended to limit the present application.

[0061] Example

[0062] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of this application. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all commercially available conventional products. This application should not be construed as being limited to the specific embodiments described.

[0063] 1. Raw materials

[0064]

[0065] 2. Testing Methods

[0066] The light source used in the experiment was a 300 W xenon lamp, with a light source distance of 6-8 cm. Circulating water was introduced into the jacket of the reaction vessel to maintain a constant temperature of 20-25 °C during the reaction. The nitrogen source used for ammonia synthesis was 99.9999% pure nitrogen gas, and the proton source was deionized water. 160 mL of deionized water and 100 mg of photocatalyst sample were added to the reactor. Nitrogen gas was first introduced into the vessel (90 mL min). -1 The reaction was carried out in darkness for 30 minutes to saturate the water with nitrogen and remove dissolved oxygen that could affect the reaction. Afterward, the mixture was stirred and exposed to light, with samples taken every 30 minutes. Each 5 mL sample was filtered through a 0.22 μm pinhole filter and then analyzed for ammonia nitrogen concentration at 450 nm using a UV spectrophotometer. A schematic diagram of the experimental setup is attached. Figure 8 As shown.

[0067] Example 1

[0068] Example 1: A method for preparing a BN / BiOBr heterojunction photocatalyst, comprising the following steps:

[0069] (1) Dissolve 0.097 g of bismuth nitrate pentahydrate in 40 mL of ethylene glycol and stir at 20~24 ℃ under closed conditions until completely dissolved to prepare a bismuth nitrate solution;

[0070] (2) Add 0.238 g of potassium bromide and 0.347 g of hexagonal boron nitride (BN) nanosheets to the bismuth nitrate solution obtained in step (1), and disperse the mixture at a mechanical stirring rate of 300-600 rpm for 30 min under closed conditions at a temperature of 20-24 ℃ to obtain a mixed dispersion.

[0071] The molar ratio of hexagonal boron nitride nanosheets to bismuth nitrate is 7:1.

[0072] (3) The mixed dispersion obtained in step (2) was subjected to a solvothermal reaction at 120 °C for 12 h. After the time was up, the precipitated product was separated by filtration. Then, the precipitated product was washed three times each with ultrapure water and anhydrous ethanol. Finally, it was dried at 70 °C for 8 h. After drying, it was ground to 20~60 mesh to prepare the BN / BiOBr heterojunction photocatalyst as a sample for testing, which was recorded as 7BN / BiOBr.

[0073] Examples 2-3, Comparative Examples 1-3

[0074] Examples 2-3 and Comparative Examples 1-3 follow the preparation method steps of Example 1, but in step (2), the amount of hexagonal boron nitride (BN) nanosheets added is used as a single variable, which are 0.050 g, 0.149 g, 0.248 g, 0.397 g, and 0.446 g, respectively, corresponding to Comparative Examples 1, 2, 3, 2, and 3. Under the above addition conditions, the molar ratio of hexagonal boron nitride nanosheets to bismuth nitrate is 1:1, 3:1, 5:1, 8:1, and 9:1, respectively.

[0075] The BN / BiOBr heterojunction photocatalyst prepared in Example 2 was used as a sample for testing and was designated as 8BN / BiOBr.

[0076] The BN / BiOBr heterojunction photocatalyst prepared in Example 3 was used as a sample for testing and was designated as 9BN / BiOBr.

[0077] The BN / BiOBr heterojunction photocatalyst prepared in Comparative Example 1 was used as a sample for testing and denoted as 1BN / BiOBr.

[0078] The BN / BiOBr heterojunction photocatalyst prepared in Comparative Example 2 was used as a sample for testing and was designated as 3BN / BiOBr.

[0079] The BN / BiOBr heterojunction photocatalyst prepared in Comparative Example 3 was used as a sample for testing and was designated as 5BN / BiOBr.

[0080] Comparative Example 4

[0081] Comparative Example 4 follows the same preparation method as Example 1, but without adding hexagonal boron nitride (BN) nanosheets in step (2), and a BiOBr photocatalyst is prepared as a sample.

[0082] After testing, such as Figures 1-2The images show scanning electron microscope (SEM) images of the photocatalyst samples prepared in Example 1 and Comparative Example 4, respectively. As can be seen from the images, the BiOBr photocatalyst prepared in Comparative Example 4 exhibits a layered microsphere structure assembled from a large number of interwoven nanosheets, forming a relatively uniform flower-like structure. In contrast, in Example 1, when a relatively high BN content was introduced, the BN nanosheets were randomly distributed on the surface of the BiOBr microspheres. Although some BiOBr microspheres were observed to aggregate, the BN nanosheets were tightly attached to the BiOBr surface, resulting in a significant increase in the interfacial contact area.

[0083] like Figure 3 The X-ray diffraction (XRD) patterns of the photocatalyst samples prepared in Example 1 and Comparative Example 4 of this invention are shown, proving that the 7BN / BiOBr obtained in Example 1 was successfully synthesized.

[0084] like Figure 4 As shown, the average ammonia formation rate of 7BN / BiOBr obtained in Example 1 reached 282.4 μmol·g. -1 ·h -1 It is approximately 14 times that of the BiOBr photocatalyst obtained in Comparative Example 4.

[0085] like Figure 5 As shown, the photocurrent response of the 7BN / BiOBr obtained in Example 1 is about 1.8 times higher than that of the BiOBr photocatalyst obtained in Comparative Example 4.

[0086] like Figure 6 As shown, the heterojunction interface in the 7BN / BiOBr obtained in Example 1 can significantly enhance the adsorption capacity of N2 and H2O molecules and increase the adsorption configuration of reactants on the catalyst surface.

[0087] like Figure 7 As shown, the comparison revealed a significant leap in the average ammonia generation rate when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions increased to 7:1. This is presumably because when the content of hexagonal boron nitride nanosheets is low, only limited interfacial contact can be formed, resulting in limited promotion of carrier separation and reactant adsorption. As the content of hexagonal boron nitride nanosheets increases, they gradually cover the surface of BiOBr microspheres, forming abundant interfacial contact regions. When the molar ratio of hexagonal boron nitride nanosheets to bismuth ions reaches 7:1, the optimal interfacial structure is obtained, which is beneficial for electron migration and surface reactions. However, when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions is further increased from 7:1, the average ammonia generation rate also drops sharply. This is presumably because excessive hexagonal boron nitride nanosheets lead to excessive electron separation, which is detrimental to subsequent reduction reactions. However, when the molar ratio of hexagonal boron nitride nanosheets to bismuth ions is further increased to 9:1, the average ammonia generation rate rebounds significantly, the reason for which is currently unknown.

[0088] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a BN / BiOBr heterojunction photocatalyst, characterized in that... Includes the following steps: (1) Dissolve bismuth nitrate pentahydrate in ethylene glycol to prepare a bismuth nitrate solution with a bismuth ion molar concentration of 0.02~0.06 mmol / mL; (2) Potassium bromide and hexagonal boron nitride nanosheets were added to the bismuth nitrate solution obtained in step (1), and a mixed dispersion was obtained after uniform dispersion; Wherein, the potassium bromide and bismuth nitrate are in equimolar amounts; The molar ratio of the hexagonal boron nitride nanosheets to bismuth nitrate is (7~9):1; (3) The mixed dispersion obtained in step (2) is subjected to a solvothermal reaction at a temperature of 120~140 ℃ for 12~16 h. After the time is reached, it is separated, washed and dried in sequence to prepare the BN / BiOBr heterojunction photocatalyst.

2. The preparation method according to claim 1, characterized in that: The hexagonal boron nitride nanosheets mentioned in step (1) are hexagonal boron nitride nanosheets with a diameter of <10 μm.

3. The preparation method according to claim 1, characterized in that: The uniform dispersion mentioned in step (2) is specifically carried out by stirring and dispersing in a closed container at a temperature of 20~24 ℃ and a mechanical stirring rate of 300~600 rpm for 20~40 min.

4. The preparation method according to claim 1, characterized in that: The steps (3) include sequential separation, washing, and drying. After drying, the process also includes grinding the material to a mesh size of 20-60.

5. The BN / BiOBr heterojunction photocatalyst prepared by the method described in claim 1.

6. The application of the BN / BiOBr heterojunction photocatalyst as described in claim 5 in photocatalytic nitrogen fixation.

7. The application according to claim 6, characterized in that: The method involves dispersing the BN / BiOBr heterojunction photocatalyst described in claim 5 in an aqueous phase to prepare a catalyst dispersion with a mass concentration of 0.4~0.8 mg / mL; introducing nitrogen gas into the catalyst dispersion at a flow rate of 50~90 mL / min; and conducting a photocatalytic reaction for 30~180 min under visible light irradiation at a wavelength of 400~700 nm and a temperature of 20~30 ℃ to synthesize NH3 from nitrogen gas via photocatalysis.